<nobr id="r1bpv"><listing id="r1bpv"><menuitem id="r1bpv"></menuitem></listing></nobr>
<pre id="r1bpv"></pre>
      <address id="r1bpv"></address>

      <em id="r1bpv"><sub id="r1bpv"><video id="r1bpv"></video></sub></em> <em id="r1bpv"><address id="r1bpv"></address></em>
        <th id="r1bpv"><noframes id="r1bpv">

          <meter id="r1bpv"></meter>
            Paul's Online Notes
            Paul's Online Notes
            Home / Algebra Trig Review / Algebra / Simplifying Rational Expressions
            Show Mobile Notice Show All Notes Hide All Notes
            Mobile Notice
            You appear to be on a device with a "narrow" screen width (i.e. you are probably on a mobile phone). Due to the nature of the mathematics on this site it is best views in landscape mode. If your device is not in landscape mode many of the equations will run off the side of your device (should be able to scroll to see them) and some of the menu items will be cut off due to the narrow screen width.

            Simplifying Rational Expressions

            Simplify each of the following rational expressions.Show All Solutions Hide All Solutions

            1. \(\displaystyle \frac{{2{x^2} - 8}}{{{x^2} - 4x + 4}}\)
              Show Solution

              There isn’t a lot to these problems. Just factor the numerator and denominator as much as possible then cancel all like terms. Recall that you can only cancel terms that multiply the whole numerator and whole denominator. In other words, you can’t just cancel the \({x^2}\) and you can’t cancel a 4 from the 8 in the numerator and the 4 in the denominator. Things just don’t work this way.

              If you need convincing of this consider the following number example.

              \[8.5 = \frac{{17}}{2} = \frac{{8 + 9}}{2} \ne \frac{{4 + 9}}{1} = 13\]

              Here is the answer to this problem.

              \[\frac{{2{x^2} - 8}}{{{x^2} - 4x + 4}} = \frac{{2\left( {{x^2} - 4} \right)}}{{{x^2} - 4x + 4}} = \frac{{2\left( {x - 2} \right)\left( {x + 2} \right)}}{{{{\left( {x - 2} \right)}^2}}} = \frac{{2\left( {x + 2} \right)}}{{x - 2}}\]
            2. \(\displaystyle \frac{{{x^2} - 5x - 6}}{{6x - {x^2}}}\)
              Show Solution

              In this one you’ve got to be a little careful. First factor the numerator and denominator.

              \[\frac{{{x^2} - 5x - 6}}{{6x - {x^2}}} = \frac{{\left( {x - 6} \right)\left( {x + 1} \right)}}{{x\left( {6 - x} \right)}}\]

              At first glance it doesn’t look like anything will cancel. However, remember that

              \[a - b = - \left( {b - a} \right)\]

              Using this on the term in the denominator gives the following.

              \[\frac{{{x^2} - 5x - 6}}{{6x - {x^2}}} = \frac{{\left( {x - 6} \right)\left( {x + 1} \right)}}{{x\left( {6 - x} \right)}} = \frac{{\left( {x - 6} \right)\left( {x + 1} \right)}}{{ - x\left( {x - 6} \right)}} = \frac{{x + 1}}{{ - x}} = - \frac{{x + 1}}{x}\]

              Also recall that

              \[\frac{a}{{ - b}} = \frac{{ - a}}{b} = - \frac{a}{b}\]

              so it doesn’t matter where you put the minus sign.

            天天干夜夜爱 天天色播 天天射天天舔 <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <蜘蛛词>| <文本链> <文本链> <文本链> <文本链> <文本链> <文本链>